Bridging classification for injury diagnoses that can be converted to both the International Classification of Diseases and the Abbreviated Injury Scale. Issue 1 (18th October 2013) - Nakahara, Shinji; Uchida, Yasuyuki; Oda, Jun; Yokota, Junichiro
Abstract : Background: The International Statistical Classification of Diseases and Related Health Problems (ICD) is currently undergoing a revision process to develop the Eleventh Revision (ICD‐11), but substantial modification of chapter 19 has not been proposed despite its known problems in describing injury severity and multiple injuries. Many facilities treating trauma patients perform duplicate coding for trauma diagnoses using two different classification systems, the ICD for administrative purposes and the Abbreviated Injury Scale (AIS) for trauma registry, because unambiguous conversion of codes between the ICD and AIS is not always possible due to structural differences. Aim: We developed a new bridging classification system which can be unambiguously converted to both ICD and AIS. Methods and Results: The bridging classification adopted multidimensional coding and addressed differences in granularity and classification boundaries by adopting the more detailed categorizations whenever the granularity and classification boundaries differed between the ICD and AIS. Then we showed that the bridging classification codes could unambiguously converted to both ICD and AIS. Conclusion: Once injuries are coded using the bridging classification, the ICD and AIS codes are readily available. Integrating the new bridging classification into the ICD‐11, possibly as a clinical modification, would eliminate the necessity of complicated procedures for code conversion and duplicate coding, and benefit users by building on the strengths of both the ICD and AIS.